Aplikasi Fuzzy Logic Mamdani Untuk Perkembangan Pertumbuhan Anak Berdasarkan BGM-KMS - Nurmuslimah, Nurmuslimah (INTEGER: Journal of Information Technology, 2016)
Considering the number of severe malnutrision cases or Balita di Bawah Garis Merah (BGM) to the deaths of children is still often happen, due to the lack of information of children growth development, service standards, and incomplete medical records also clinic rules that aren't obeyed. Example case is focused on Kartu Menuju Sehat (KMS).Decision making system for this BGM-KSM based children growth development is very appropriate to be applied on problems handling which need solution from computer to process toddlers data with rapid and accurate calculation. So the decision making system which can be used is Fuzzy Logic Mamdani reasoning.Fuzzy Logic Mamdani is also known as max-min method which can search for fuzzy set from fuzzy rule composition, while the output is resulted from that fuzzy set's domain. To modify the output from fuzzy numbers to firm numbers or defuzzytion using Centroid (Composite Moment) method which is used to search for Centre of Area (COA). This research is conducted to get fuzzy rule value, and then to determine health state and get the solution of energy/calori needed based on age, body weight, and body height.